Landscape structure and live fences in Andes Colombian agrosystems: upper basin of the Cane-Iguaque River - Javier Otero; Miren Onaindia (Revista de Biología Tropical, 2009)
Changes in land use have generated a new landscape configuration in the Andino orobiome (mountain range) of the tropical Andes, resulting in a mosaic of cultivation and pastures interrupted by small fragments of forest and live fences. This has resulted in an ongoing decrease in the biodiversity of this biome. In the upper basin of the Cane-Iguaque River (Villa de Levya-Boyacá, Colombia), located 2 600-3 000 m above the Cordillera Oriental, over three time periods in 1960, 1984, and 2004, we characterized the structure, patterns, and evolution of the overall landscape and of the live fences (used as tools in biodiversity conservation and considered to be desirable alternatives to nonlive fences in farming production systems) within an agricultural landscape. To do this, we interpreted high- resolution satellite images using a landscape ecology approach and applied landscape map metrics. We found that the natural forests have been transformed by pastures and cultivation, and that although live fences cover only a small portion of the total landscape (4.6%), they have an important effect on landscape structure and biodiversity. There has been an increase in live fences, especially between 1960 and 1984, as well as an increase in their density. However, there has been a reduction in the average length of live fences over the periods that we studied. This could be due in part to changes in the types of agricultural products that have been cultivated in recent years, with an increase in potatoes and a decrease in other vegetables, and also by resource extraction of timber and fuel wood. In the studied area, agricultural production was sustained while biodiversity conservation was improved by the use of live fences. Therefore, live fences should be considered not only as part of an agriculturally productive area, but also as an important element of a multi-functional landscape that contributes to the maintenance of biodiversity and provides resources of economic and ecological interest, decreasing the pressure on natural forest. Improving the network of live fences constitutes an important strategy for the sustainable management of the rural landscape of the Andino orobiome of Colombia and similar areas in the tropics. Rev. Biol. Trop. 57 (4): 1183-1192. Epub 2009 December 01. El cambio del uso del suelo ha generado una nueva configuración del paisaje en el Orobioma Andino de los Andes tropicales, dando lugar a un mosaico de cultivos y potreros interrumpidos por pequeños fragmentos de bosque y cercas vivas, con la disminución sobre la biodiversidad de este bioma. En la cuenca alta del río Cane- Iguaque (Boyaca-Colombia), ubicada entre 2 600-3 000 metros de altitud sobre la cordillera Oriental, se realizó un estudio de caracterización de estructura, patrones y evolución del paisaje y de las cercas vivas, en tres periodos 1960, 1984 y 2004, como herramienta para la conservación de la biodiversidad y alternativa en el manejo de los sistemas agrícolas. Se utilizó una metodología de interpretación de imágenes de satélite de alta resolución, bajo el enfoque de la ecología del paisaje y la utilización de métricas del paisaje. El bosque original esta altamente transformado por pastizales y cultivos, las cercas vivas ocupan apenas el 4.6% del área de estudio pero por su distribución se constituyen en elementos importantes para la biodiversidad. Se observa un incremento en las cercas vivas, entre los años 1960 y 1984. Sin embargo en este mismo período se da una disminución en la longitud, debido a la tendencia de aumento en el cultivo de papa y por la extracción de recursos de madera y leña. Para la zona de estudio es muy importante la producción agrícola y la conservación de la biodiversidad, y puede ser mejorada mediante la utilización de cercas vivas. Por tanto, las cercas deben considerarse como elementos multifuncionales del paisaje que contribuyen en el mantenimiento de la biodiversidad y aportan recursos de interés ecológico y económico, atenuando la presión sobre los bosques originales. El manejo adecuado y la mejora de la red de cercas vivas se constituyen en estrategias importantes para la gestión sostenible de paisaje rural de la zona andina colombiana.